South Carolina petitions for state roads
Petitions for the construction of state roads and bridges in South Carolina.
Negative photocopies and facsimilies.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bridges -- South Carolina -- Design and construction; Public works -- South Carolina; Roads -- South Carolina -- Design and construction